THE COMMITMENT BEHAVIOR OF FISHERS TOWARDS THE DEVELOPMENT OF THEIR COMMUNITY A Case Study in Demak Central Java – Indonesia - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 2003)
The commitment of fishers towards their community development is investigated in this study. Several statistical tools such as discriminant analysis, cross-tabulation  and compare means  with  independent t-test have been employed  to analyze the data which were collected from 56 samples in the study area of  Wedung and Moro Demak, Demak Regency.  The results  showed  that  the commitment behaviour  of fishers  might be guided  by several variables  such as  Age, Sex, Educ, Exper, Inc, Stay.  In order  to improve the commitment levels of respondents,  thus, magnitude of  the observed variables in the model could be explored further.  Lastly, the model of fishers’ commitment with discriminant analysis performes fairly good with  the right prediction of the original grouped cases is correctly classified for about 62.5%.